Pemekaran Wilayah Dalam Kuasa Wacana Elite Politik Lokal (Studi Kuasa Wacana Pemekaran Wilayah Kabupaten Bogor Timur Oleh Elite Politik Lokal Tahun 2016-2019) - Hamidah, Siti Basrah; Ali Azhar, Muhammad; Noak, Piers Andreas (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2021)
ABSTRACT This study analyzes the division of regions in the discourse of the power of local political elites in East Bogor in 2016-2019. This study uses the theory and methods of Norman Fairclough's Critical Discourse Analysis with this type of qualitative research. The analysis is divided into 3 dimensions, namely text analysis, discourse practice, and social practice. The results of this research are in the form of text analysis, namely when the text begins to be published to the public, the discourse develops and social practices will support the developing discourse. Social practices that are influential in strengthening the power of discourse which in turn can encourage community decisions to agree with the discourse on regional expansion. This research answers, about how the discourse on the expansion of the area of ??East Bogor Regency is used by local political elites in influencing community decisions by embracing other parties. Keywords: regional expansion, discourse power and local political elite